Pengaruh Kinerja Keuangan Terhadap Pelaporan Terintegrasi : Studi Kasus di Perusahaan Pertambangan Yang Terdaftar Di BEI - Afi Masruroh; Karina Sekar Rachmadanti; Nindya Cahya Puspita; Maria Yovita R. Pandin (Akuntansi, 2024)
This study aims to evaluate the influence of financial performance on integrated reporting in the Indonesian mining sector listed on the Indonesia Stock Exchange (BEI). The study employs a case study approach to examine selected mining companies. Data is gathered from detailed financial statements and integrated reports owned by the companies during the period of 2020-2022. The analysis results indicate that integrated reporting positively contributes to the companies' financial achievements.